2020
DOI: 10.1128/msystems.00809-20
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Succession of Polymicrobial Communities in the Cystic Fibrosis Airways

Abstract: Antimicrobial therapies against cystic fibrosis (CF) lung infections are largely aimed at the traditional, well-studied CF pathogens such as Pseudomonas aeruginosa and Burkholderia cepacia complex, despite the fact that the CF lung harbors a complex and dynamic polymicrobial community. A clinical focus on the dominant pathogens ignores potentially important community-level interactions in disease pathology, perhaps explaining why these treatments are often less effective than predicted based on in vitro testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 159 publications
(220 reference statements)
1
37
0
Order By: Relevance
“…With enough data, the geometry of these systems (i.e., states that are connected to each other, indicating the possibility of a transition) can be determined. In this context, Markov models can be used to identify parallels between our longitudinal cohort and accepted models of ecological succession in the cystic fibrosis airway ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…With enough data, the geometry of these systems (i.e., states that are connected to each other, indicating the possibility of a transition) can be determined. In this context, Markov models can be used to identify parallels between our longitudinal cohort and accepted models of ecological succession in the cystic fibrosis airway ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…In CF children, the background network was found to be underdeveloped and the majority of rare species in CF airways was associated with the toddler age group (1–3 years of age). Since a close-to-healthy network structure of high-abundant taxa was only detected in CF toddlers, a long-term immune system stimulation is missing in CF pre-school children for most of the time and the training of the immune system is defined by non-persisting bacteria or pathogens later in life [37] , [64] , [65] . Leitão et al (2016) [23] utilised simulation studies of environmental ecosystems and thereby unravelled the disproportional influence of rare species on the functional structure of an ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that rare species extinction causes a disturbance on the long-term supply of goods and services and thus destabilises the entire ecosystem [23] . The detection of the majority of rare species in CF toddlers with their subsequent loss in pre-schoolers may hence explain the known reduction in core species diversity and occurrence of network fragmentation as the disease progresses [37] , [64] , [65] , [66] . Furthermore, the loss of rare species may create an open niche in the CF airway habitat that can be chronically filled by incoming CF hallmark pathogens such as P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…However, because the lung microbiome is polymicrobial ( Erb-Downward et al., 2011 ; Beck et al., 2012 ; Wilkinson et al., 2017 ) this diversity may facilitate complex but poorly understood interspecific interactions between bacteria as well as viruses ( Molyneaux et al., 2013 ). These interspecific interactions ( Figure 2 ) may be indirect, through changing of both biotic and abiotic conditions that favour the proliferation of secondary colonisers in airways diseases, analogous to ecological succession ( Khanolkar et al., 2020 ). For example, NTHi infection has been found to upregulate the pro-inflammatory responses that may drive wider microbial shifts and exacerbate COPD ( Rotta Detto Loria et al., 2013 ; Staples et al., 2016 ) as well as upregulate MUC2 production, increasing airway obstruction and providing a viscous substrate for secondary bacterial colonisers ( Zhang et al., 2020 ) over time.…”
Section: Nthi Biofilm Strategiesmentioning
confidence: 99%